The Impact of Hospital Administration on Healthcare Workforce Development and Training Programs - Dahlan, Andini Fatikasari; Ummi, Sri Hajartul; Mustari , Muh Iqbal (ScieClouds Publishing, 2024)
A research analysis examines how hospital administrative approaches affect programs which develop and train medical staff. This research studied the relationship between administrative factors such as leadership approaches and resource advantages and employee development support which determine workforce training initiative performance. A total of 450 healthcare professionals took part in the survey which targeted medical staff in both public and private hospitals operating in different service types and sizes within the region. The researchers analyzed the data using descriptive and inferential statistical procedures which included Pearson’s Correlation Coefficient, Multiple Regression Analysis as well as One-Way ANOVA. The research demonstrated that leadership approaches together with financial support allocation and administrative collaboration positively affected the workforce development outcomes through improved staff performance and enhanced motivation and higher job satisfaction. Training results varied between different hospital settings because larger institutions demonstrated better outcomes during the study. The research results emphasize how well-planned administrative procedures enhance the performance levels of workforce development initiatives. The research adds evidence-based knowledge about hospital administration-role training relationships while providing actionable recommendations to healthcare leaders who want to enhance their training programs. Future research needs to analyze time-based data along with cultural influences and resource management challenges to develop strategies which enhance healthcare employee training programs